2011
DOI: 10.1590/s0006-87052011000200016
|View full text |Cite
|
Sign up to set email alerts
|

Sensibilidade de fungos entomopatogênicos a agroquímicos usados no manejo da cana-de-açúcar

Abstract: ResumoOs agroquímicos empregados no manejo da cana-de-açúcar podem afetar a ação de fungos entomopatogênicos usados no controle biológico de pragas da cultura. Este trabalho teve por objetivo investigar se os inseticidas, herbicidas e maturadores utilizados no manejo da cana-de-açúcar têm efeito tóxico sobre os fungos Beauveria bassiana e Metarhizium anisopliae. Foram utilizados os inseticidas thiametoxan, aldicarbe e fipronil, os herbicidas imazapir, diuron, metribuzin, hexazinone+diuron, clomazone+ametrina, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
0
7
0
5
Order By: Relevance
“…The compatibility of azadirachtin and thiamethoxam, ranked within the tetranortriterpenoide and neonicotinoid chemical groups, respectively, with the isolates of the entomopathogenic fungus B. bassiana, I. sinclairii, and M. rileyi could be related to the low toxicity of these chemical molecules for microorganisms, but also by the possible capacity of entomopathogen to degrade these compounds aiming development and reproduction (Batista Filho et al 2001, Botelho and Monteiro 2011, Hern andez et al 2012, Niassy et al 2012, Santos et al 2013, Silva et al 2013. Different studies have shown the possibility of using these active ingredients with different species of entomopathogenic fungi, showing positive results on the issues focused on compatibility (Batista Filho et al 2001, Andal o et al 2004, Botelho and Monteiro 2011, Hern andez et al 2012, Ribeiro et al 2012, Rocha et al 2012, Cintra et al 2013.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compatibility of azadirachtin and thiamethoxam, ranked within the tetranortriterpenoide and neonicotinoid chemical groups, respectively, with the isolates of the entomopathogenic fungus B. bassiana, I. sinclairii, and M. rileyi could be related to the low toxicity of these chemical molecules for microorganisms, but also by the possible capacity of entomopathogen to degrade these compounds aiming development and reproduction (Batista Filho et al 2001, Botelho and Monteiro 2011, Hern andez et al 2012, Niassy et al 2012, Santos et al 2013, Silva et al 2013. Different studies have shown the possibility of using these active ingredients with different species of entomopathogenic fungi, showing positive results on the issues focused on compatibility (Batista Filho et al 2001, Andal o et al 2004, Botelho and Monteiro 2011, Hern andez et al 2012, Ribeiro et al 2012, Rocha et al 2012, Cintra et al 2013.…”
Section: Resultsmentioning
confidence: 99%
“…(Gopalakrishnan 1989, Silva et al 2003, Godonou et al 2009, Xu et al 2011, Méndez 2012. One of the barriers to using more efficient and also the conservation of these microbial agents in the field is related to the compatibility with the pesticides used to control other pests or agricultural diseases (Batista Filho et al 2001, Almeida et al 2003, Batista Filho et al 2003, Cuthbertson et al 2005, Botelho and Monteiro 2011, Niassy et al 2012, Schumacher and Poehling 2012.…”
mentioning
confidence: 99%
“…Resultados de completa inibição desse produto também foram encontrados por outros autores (Andaló et al, 2004;Botelho;Monteiro, 2011); com isso os índices biológicos foram zero, classificando esse produto como tóxico para todos os isolados de B. bassiana avaliados. Andaló et al (2004) e Botelho;Monteiro (2011) também classificaram esse produto como tóxico para B. bassiana, sugerindo, assim, a existência de grande risco ou impacto para o fungo na utilização indiscriminada desse herbicida.…”
Section: Resultsunclassified
“…De modo contrário, Botelho & Monteiro (2011) observaram redução na esporulação de Beauveria bassiana e Metharizium anisopliae após aplicação do imazapyr -inibidor da ALS.…”
Section: Impacto De Herbicidas Em Isolados De Trichoderma Sppunclassified
“…Entretanto, foram detectados efeitos de herbicidas, por exemplo, com apenas 25% da dose recomendada de thiobencarb + propanil, com redução de quase 50% do crescimento micelial radial. Embora, de acordo com Botelho & Monteiro (2011), os mecanismos de inibição de microrganismos pelos herbicidas sejam ainda pouco conhecidos, neste e em outros trabalhos foram constatados efeitos adversos de pesticidas aos organismos não alvo. Ressalta-se que é necessário que haja integração e averiguação da compatibilidade dos métodos de controle de doenças, pragas e plantas daninhas para que se possa realizar um manejo integrado eficiente e pouco impactante ao ambiente.…”
Section: Impacto De Herbicidas Em Isolados De Trichoderma Sppunclassified